The role of triple helix synergy, access to capital, and financial literacy on sustainable MSMEs economic growth - Arif, Muh; Amir, Amir; Sharon, St Salmah; Basir, Mustika Kusuma (Universitas Muhammadiyah Yogyakarta, 2026)
In the context of increasing economic uncertainty, digital disruption, and the global transition toward a green economy, understanding the key drivers of sustainable Micro, Small, and Medium Enterprise (MSME) growth remains a critical research agenda, particularly in developing economies where MSMEs serve as the backbone of economic resilience. This study aims to analyse the influence of triple helix synergy, access to capital, and financial literacy on sustainable MSME economic growth. The research employs a quantitative approach using Partial Least Square (PLS) analysis on MSME actors. The results indicate that the measurement model meets the required validity and reliability criteria. Furthermore, the structural model reveals that triple helix synergy and financial literacy have a significant positive effect on sustainable MSME economic growth, while access to capital does not show a significant influence. These findings highlight that sustainable MSME growth is not merely determined by the availability of financial resources but is more strongly driven by effective cross-sector collaboration and the capacity of MSME actors to manage financial resources in an accountable and strategic manner. The study confirms that collaboration among government, academia, and businesses, alongside enhanced financial literacy, plays a crucial role in fostering sustainable economic growth of MSMEs. Accordingly, this research underscores the importance of integrating institutional synergy and financial capability development as strategic policy instruments to strengthen MSME competitiveness in the green and digital economy era.